Методы и приёмы ТРКМЧП при изучении рассказов К.Паустовского «Барсучий нос», «Кот-ворюга» в национальных классах общеобразовательной школы - Ешниязова, Э.Н. (SCIENCE and SOCIETY, 2019)
The article deals with current issues in the methodology of teaching Russian literature in a national school. The questions of the application of the technology for the development of critical thinking through reading and writing when studying the stories of K. Paustovsky "Badger Nose", "Cat-thief" in the 5th grade of a secondary school have been studied.
Keywords: lesson; literature; integration; art pedagogics; methods and techniques; critical thinking; K.Paustovskiy; national class